Pertanggung Jawaban Pidana Penipuan Analisis Putusan Pengadilan Tinggi Tanjung Karang Nomor : 381/PID/2025/PT. Tjk - Januri Januri; Alfi Hizamizi; Hendika Saputra; Rizal Simarmata (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze criminal liability in fraud cases based on the Decision of the Tanjung Karang High Court Number: 381/PID/2025/PT. Tjk. This study explores judges’ legal considerations in assessing the fulfillment of fraud elements and the application of criminal liability principles to the defendant. Research Methodology: This study uses a normative juridical approach with a descriptive-analytical specification. Secondary data, including court decisions, statutory regulations, and relevant legal literature, were used for the analysis. Results: The study finds that the panel of judges declared the defendant guilty beyond a reasonable doubt for fulfilling the elements of fraud, as outlined in Article 378 of the Indonesian Criminal Code. The defendant was proven to have unlawfully benefited from deception or a series of lies that induced the victim to surrender their property. The judges' reasoning was based on lawful evidence, consistent with Article 184 of the Indonesian Criminal Procedure Code, and their conviction was derived from the facts presented at trial. Conclusions: The application of criminal liability in this case aligns with the principles of legality, culpability (geen straf zonder schuld), and criminal responsibility theory within Indonesian criminal law. Limitations: This study is limited to analyzing a single court decision, which may not fully reflect the broader trends in fraud criminal liability cases. Contributions: This research contributes to the understanding of judicial reasoning in fraud cases and the application of criminal liability principles, enriching the legal discourse on fraud offenses in Indonesia.